Disinfection of Surfaces Contaminated with SARS-CoV-2 Coronavirus by UV Radiation of Low-Pressure Mercury-Vapour Lamp - D. N. Masyakin; A. E. Alferov; S. G. Kikot’; I. A. Androshchuk; V. B. Kirillov; S. L. Kirillova; E. A. Koval’chuk; M. A. Kotov; V. А. Lopota; I. G. Rudoy; N. G. Solov’ev; A. M. Soroka; et al. (Проблемы особо опасных инфекций)
The aim of the work was to determine the effective ultraviolet (UV) doses required for the disinfection of surfaces contaminated with the SARS-CoV-2 coronavirus using a low-pressure mercury lamp. Materials and methods. To carry out prompt disinfection of surfaces, a specially designed source of UV radiation with a power of 7.5 W at a wavelength of 254 nm in the form of a portable flashlight was employed, which has a high efficiency of UV radiation output and the possibility of long-term autonomous operation from a compact battery. In the studies, a suspension culture of the SARS-CoV-2 coronavirus with biological activity of 5.3∙106 PFU/ml was used. The objects of testing were plastic Petri dishes (disposable) and office paper (grade C, density 80 g/m2 ). Results and discussion. Doses of UV radiation that provide disinfection of surfaces contaminated with the COVID-19 pathogen with an efficiency of 99.0 % (paper) to 99.95 % (plastic) have been determined. The results obtained make it possible to recommend a portable UV irradiator for use in the practice of preventive measures to combat the spread of the disease caused by the SARS-CoV-2 coronavirus.